SEMIOTICS PROGRESS IN TRADITIONAL-GAME-BASED NUMBER LEARNING FOR PRIMARY SCHOOL STUDENTS - Nasrullah . (Jurnal Cakrawala Pendidikan, 2015)
Abstract: This study was aimed at describing the students’ semiotic progress on learning number by using traditional games of Bermain Satu Rumah (BSR) supported by a set of learning activities based on Indonesian Realistic Mathematics Education. The study was designed into three stages, that is, the preliminary design, the teaching experiment, and the retrospective analysis. Then, Hypothetical Learning Trajectory (HLT) was modified as the reference of this study as well as the research instrument. HLT was tested to 24 third graders. The data were collected by applying the interview technique, observation, and field notes. The findings of the study showed that this instructional design could motivate students to join learning activities and could stimulate them to conserve the context, to understand the symbol meaning and use it, and to communicate starting from the informal to the formal levels. The progress was on the ability of students to abstract by holding and using symbols as a part of plan to solve the problem. Keywords: semiotics, bermain satu rumah, hypothetical learning trajectory, learning numbers KEMAJUAN SEMIOTIKA DALAM PEMBELAJARAN BILANGAN BERBASIS PERMAINAN TRADISIONAL BAGI SISWA SEKOLAH DASAR Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemajuan semiotika siswa dalam pembelajaran bilangan dengan menggunakan permainan tradisional Bermain Satu Rumah yang didukung dengan serangkaian aktivitas belajar berdasarkan Pendidikan Matematika Realistik Indonesia. Penelitian didesain melalui tiga fase, yaitu desain awal, eksperimen mengajar, dan analisis retrospektif. Dugaan Lintasan Belajar dibuat sebagai acuan dalam pelaksanaan penelitian sekaligus menjadi instrumen penelitian. Dugaan Lintasan Belajar diujikan kepada 24 orang siswa kelas III SD. Pengumpulan data dilakukan dengan menggunakan teknik wawancara, pengamatan, dan catatan lapangan. Hasil penelitian menunjukkan desain pembelajaran ini dapat memotivasi siswa untuk mengikuti kegiatan pembelajaran dan dapat merangsang siswa untuk mengonservasi konteks, memahami makna simbol dan menggunakannya, serta mengomunikasikan mulai dari tahap informal sampai formal. Kemajuan yang ditemukan adalah kemampuan siswa untuk mengabstraksi dengan mengadakan dan menggunakan simbol sebagai bagian dari rencana untuk menyelesaikan masalah. Kata Kunci: semiotik, bermain satu rumah, dugaan lintasan belajar, pembelajaran bilangan